Prevalence of hypertension and glycaemic control in adult type-2 diabetes patients: A preliminary retrospective cohort study in Kuantan, Pahang, Malaysia - Abdullah, Fa’iza; Tin, Myo Han; Mat Nor, Mohd Basri; Md Aris, Mohd Aznan; Ismail, Ida Zuriaty (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2017)
Introduction: Hypertension (HPT) is the most common co-morbidity among type-2 diabetes mellitus (T2DM) patients which ominously increased their morbidity and mortality from cardiovascular diseases (CVD). We aimed to determine the prevalence and control status of HPT, and also the glycemic control among T2DM patients in a primary care clinic in Kuantan, Pahang. Methods: It was a retrospective study of 154 T2DM patients’ records, aged ≥18 years selected by random sampling. The statistical analysis is done by using Chisquare test, paired sample “t” test and ANOVA “F” test. Results: Among T2DM patients; 47% were Malay, 45% Chinese and 9% Indian. The prevalence of HPT was 72.1% and majority of T2DM patients were women (60%). Out of 82 T2DM aged >60 years, 80.5% were hypertensive. 67.2% of T2DM patients between the age of 40-60 years and 25% age <40 years were also hypertensive (p= 0.003). BP-controlled status were classified into controlled, uncontrolled, systolic and diastolic HPT. All patients were compared between the last visit and one year before, which reported 55.8% versus 33.1%, 14.9% versus 51.9%, 20.1% versus 10.4% and 9.1% versus 4.5% respectively. There were significant rises in percentage of systolic BP (by 9.7%) and diastolic HPT (by 4.6%) p<0.0001, from the first visit. BP controlled status for aged group >60 years showed increments in systolic HPT and diastolic HPT which were significant (p<0.0001). Regarding glycemic parameters, 71.4% T2DM patients had poor controlled level of Hb1Ac (≥6.5) and only 20.1% remained controlled after one year (p<0.0001). Conclusions: This pilot study found high prevalence of HPT, increasing prevalence of systolic HPT and diastolic HPT in older age group as well as poor glycemic control among T2DM patients.